The challenge of progress : theory between critique and ideology - Dahms, Harry F. (Bingley, U.K. : Emerald Publishing Limited, 2019)
Globalization has accelerated the process of social, political, cultural, and especially economic transformations since the 1990s. In recent decades, this has cast doubt over the validity and reliability of many working assumptions about the nature and logic of progress in modern societies, at all levels of social structure and complexity. In The Challenge of Progress, editor Harry F. Dahms and a series of contributors explore how this doubt has been magnified, looking at how the institutions and constellations between business, labor and government have begun to weaken. The essays included in this volume examine the foundations, nature and contradictions of progress in the modern era. Anchored by - but not exclusively focused on - a debate of Amy Allen's recent book, The End of Progress: Decolonizing the Normative Foundations of Critical Theory (2016), the eleven essays identify, analyse and confront the challenges of progress, looking across social class, philosophy, history and culture in their analyses. For researchers and students across social theory, this is an unmissable volume confronting the present and future of our societies. Examining the choices of modern society, Dahms and contributors ask: what are the social costs of "progress"?
Introduction -- Part I: Identifying the challenge: a critical discussion of the end of progress: decolonizing the normative foundations of critical theory (2016) / by Amy Allen -- 1. History, critique and progress: Amy Allen's 'end of progress' and the normative grounding of critical theory / Reha Kadakal -- 2. Inheriting critical theory: a review of Amy Allen's the End of progress: decolonizing the normative foundations of critical theory / George Steinmetz -- 3. Back to Adorno: critical theory's problem of normative grounding / Karen Ng -- 4. Decolonizing critical theory / Kevin Olson -- 5. Progress, normativity, and the "decolonization" of critical theory: reply to critics / Amy Allen -- Part II: Assessing the challenge: progress, politics, and ideology -- 6. Nietzsche after Charlottesville / Robert J. Antonio -- 7. "How can [we] not know?" Blade Runner as cinematic landmark in critical thought / Lawrence Hazelrigg -- 8. Sociology at the end of history: profession, vocation and critical practice / Daniel M. Harrison -- Part III: Confronting the challenge: the dynamics of progress in the modern age -- 9. Las Vegas as the anthropocene: the neoliberal city as desertification all the way down / Timothy W. Luke -- 10. Exchanging social change for social class: traditional marriage proposals as status and scrip / Patricia Arend and Katherine Comeau -- 11. Sociology's emancipation from philosophy: the influence of Francis Bacon on Emile Durkheim / Shawn van Valkenburgh -- About the contributors -- Index.
Includes index.
Print version record.
Keywords: Progress; Social change; Globalization; Social Science -- Sociology -- General; Sociology